Augmented Reality untuk Meningkatkan Keterampilan Menulis, Berbicara, Keterampilan Berpikir Kritis dalam Pembelajaran Bahasa Indonesia Kelas V SD Xyz Bintaro - Wahyu Wasono Putro; Pujianto Yugopuspito (Syntax Corporation Indonesia, 2024)
Students need to learn thoroughly on the writing, speaking and critical thinking skills in order to adapt with the development of technology and information. This study aims to analyze the differences between 2 classes that implemented 2 different means in learning Bahasa Indonesia for grade 5 students, between control class that use lecturing method and the experiment class that use Augmented Reality. The research subject were the fifth graders of XYZ school in Bintaro area. There were 28 students from control group and 27 students from the experiment group with a total of 55 students in all. This research period was conducted in 4 months from late January in 23 January 2024 to 10 May 2024. This study used a weak experimental design method with a static-group pretest-posttest design model. The research data was collected from the observation of the students performance during class discussion and project presentation which used a rubric that has been validated and is a reliable instrument. The result of the statistical analysis showed differences in the control class pretest and control class posttest, in the experimental class pretest and experimental class posttest, also the nGain result for both classes in writing, speaking and critical thinking skills. The average nGain for control class in writing, speaking and critical thinking skills respectively are; 0,17; 0,21; 0,26 While the average nGain for the experiment class in writing, speaking and critical thinking skills is 0,41; 0,31; 0,27 respectively. Based on the result, the ngain result for critical thinking skills in experiment class showed low result using 0,3 as the significance value. This result means the use of Augmented Reality was less effective in critical thinking skills but effective in writing and speaking skills.